أثر انموذج اثرارئي ثلاثي الابعاد في حل المسائل الرياضية لدى طالبات المرحلة المتوسطة - رفاه; دعاء (مجلة كلية التربية, 2020)
The present study aims at identifying the effect of The Effect Enrichment Traid Model in the solving Mathematical problems for secondary school female student .The model consists of three phases: discoverying activites,group work ,indivival work.The sample of the present study consists of (67 ) female student divided two groups.( 34) represent The class control groups (34) femal while experimental groupa (33)femal The sample consists of (67) female students have been chosen from the first class intermediate in AL-Mutmaizat smart secondary school for girls,. And it has been equalized in the variables(previous achievement in mathematics, test previous knowledge ,intelligence). the rserch tool consist Booklet Enrichment from the book of math topics in accordance with the three dimensions the Enrichment Traid Model while the second and test solving mathematical problems be from 18 items of the essay questions, after obtaining the t-test (validity and reliability) The results showed using t-test and there is a statistically significant differences at the level of 0.05 for the experimental group depending on the study results, a number of recommendation are made such as emphasize the importance of the Enrichment Traid Model in solving mathematical problems as a way of taking care of the smart student a mong the other ways. Also suggestions for farther studies have been drawn such as contucting more studies to identify the effect of this model on the other variable like with othwer subject.